Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Remarkable structural resistance of a nanoflagellate-dominated plankton community to iron fertilization during the Southern Ocean experiment LOHAFEX - Schulz, Isabelle; Montresor, Marina; Klaas, Christine; Assmy, Philipp; Wolzenburg, Sina; Gauns, Mangesh; Sarkar, Amit; Thiele, Stefan; Wolf-Gladrow, Dieter; Naqvi, Wajih; Smetacek, Victor (Marine Ecology Progress Series, 2018)
The genesis of phytoplankton blooms and the fate of their biomass in iron-limited, high-nutrient-low-chlorophyll regions can be studied under natural conditions with ocean iron fertilization (OIF) experiments. The Indo-German OIF experiment LOHAFEX was carried out over 40 d in late summer 2009 within the cold core of a mesoscale eddy in the productive south-west Atlantic sector of the Southern Ocean. Silicate concentrations were very low, and phytoplankton biomass was dominated by autotrophic nanoflagellates (ANF) in the size range 3-10 µm. As in all previous OIF experiments, the phytoplankton responded to iron fertilization by increasing the maximum quantum yield (Fv/Fm) and cellular chlorophyll levels. Within 3 wk, chlorophyll levels tripled and ANF biomass doubled. With the exception of some diatoms and dinoflagellates, the biomass levels of all other groups of the phyto- and protozooplankton (heterotrophic nanoflagellates, dinoflagellates and ciliates) remained remarkably stable throughout the experiment both inside and outside the fertilized patch. We attribute the unusually high biomass attained and maintained by ANF to the absence of their grazers, the salps, and to constraints on protozooplankton grazers by heavy predation exerted by the large copepod stock. The resistance to change of the ecosystem structure over 38 d after fertilization, indicated by homogeneity at regional and temporal scales, suggests that it was locked into a stable, mature state that had evolved in the course of the seasonal cycle. The LOHAFEX bloom provides a case study of a resistant/robust dynamic equilibrium between auto- and heterotrophic ecosystem components resulting in low vertical flux both inside and outside the patch despite high biomass levels. KEYWORDS: Antarctic · Protists · Fe-limitation · Si-limitation · Ecology-biogeochemistry relationship · Carbon:chlorophyll ratios · Ecosystem stability
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; økologi; økosystemer